Improving the Utility of Large-Scale Assessments in Canada - Rogers, W. Todd (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
Principals and teachers do not use large-scale assessment results because the lack of distinct and reliable subtests prevents identifying strengths and weaknesses of students and instruction, the results arrive too late to be used, and principals and teachers need assistance to use the results to improve instruction so as to improve student learning. Therefore, it is recommended that the first assessment activity should be to clearly establish that the domain to be assessed is multidimensional. Given this, the assessment schedule should be changed so that a given subject area is assessed in non-consecutive years but the number of sittings remains the same each year. Assistance should be provided to principals and teachers so as to increase their understanding of how to use large-scale assessment results. Three suggested assessment cycles are presented, each of which increases the reliability of subtests and provides principals and teachers with at least two years to make changes in instruction.